Time to live of identifier‐to‐locator mappings: with‐reset or no‐reset. (5th December 2012) - Li, Xiaoqian; Zukerman, Moshe; Zhou, Huachun; Luo, Hongbin; Qiu, Feng; Zhang, Hongke
SUMMARY In networks with identifier/locator separation, border routers often cache recently used identifier‐to‐locator mappings of remote hosts and set a time to live (TTL) for each mapping. We consider two options to update the TTL of a mapping, designated as no‐reset (NR) and with‐reset (WR) modes. In the NR mode, once a mapping is cached, its TTL is set to a default value called cache timeout, and the mapping is removed when the TTL expires. By contrast, in the WR mode, whenever the mapping is queried, its TTL is reset to the cache timeout. Although it is not difficult to intuitively observe that the WR mode performs better than the NR mode in terms of cache hit rate, it is still of interest to evaluate what is the benefit gained by using the WR mode rather than the NR mode and what is the cost incurred to achieve this gain. Another equivalent question is what is the additional cost incurred in terms of resources for the NR mode to perform similarly to the WR mode. We model the cache hit rate and compare the performance of the WR and NR modes for flat and aggregatable identifiers by analysis and simulation, and estimate how much more cache size the NR mode requires to achieve similar cache hit rate and communication interruptions to the WR mode. The comparison results provide rational to use the WR mode, rather than the NR mode, for identifier‐to‐locator mapping caches. Copyright © 2012 John Wiley & Sons, Ltd.